Biohacking and the risks of gray market peptides - O'Grady, Mitchell (My University, 2026)
This opinion editorial examines the growing popularity of biohacking and the risks associated with unregulated synthetic peptides sold through gray market channels. While biohacking is often promoted as a method of optimizing health, performance, and wellbeing, many experimental peptides are marketed online despite limited scientific evidence regarding their safety and efficacy. The paper explores how social media influencers, online wellness communities, and algorithm-driven platforms contribute to the normalization and promotion of these substances. Drawing on research from public health, pharmacology, ethics, and media studies, the editorial discusses concerns related to product quality, misinformation, regulatory oversight, and consumer safety. Particular attention is given to the role of influencer credibility and the increasing availability of peptides marketed as “research chemicals” or substances “not for human consumption.” The paper argues that stronger regulatory oversight, improved digital health literacy, greater platform accountability, and consultation with licensed healthcare professionals are necessary to reduce the risks associated with gray market peptide use.
Keywords: biohacking; experimental peptides; gray market peptides; safety and efficacy